CLINICAL CHARACTERIZATION OF STARGARDT DISEASE PATIENTS WITH THE p.N1868I ABCA4 MUTATION. Issue 12 (December 2019) - Collison, Frederick T.; Lee, Winston; Fishman, Gerald A.; Park, Jason C.; Zernant, Jana; McAnany, J. Jason; Allikmets, Rando
Abstract : Purpose: To investigate the Stargardt disease phenotype associated with an unusually common and "extremely hypomorphic" ABCA4 variant, p.N1868I. Methods: The charts of 27 patients with p.N1868I on one allele and a severe/deleterious mutation on the other allele were reviewed. Subjective age of onset, best-corrected visual acuity, and stage of disease were recorded for all 27 patients, 18 of whom had multiple visits. When available, fundus photography, spectral domain optical coherence tomography, fundus autofluorescence, full-field electroretinograms, Goldmann visual fields, and fluorescein angiography were included. Five families with multiple affected members were analyzed. Results: The median age at symptom onset was 41.5 years, and 3 p.N1868I patients had not developed visual symptoms as of the most recent eye examination. Median best-corrected visual acuity in the better-seeing eye at baseline was 20/25 −2, and the median duration from symptom onset to legal blindness was 25 years. The five families described in this study demonstrated clinically significant intrafamilial variability, and affected family members who did not share the p.N1868I variant had relatively more severe phenotypes. Conclusion: This study demonstrates the consistency of foveal sparing, the variation in age at onset, the intrafamilial variability, and the prognosis with regard to visual acuity in p.N1868I-associated Stargardt disease. Abstract : An "extremely hypomorphic" ABCA4 variant, p.N1868I, which is unusually common in the general population, is highly associated with foveal-sparing and late-onset Stargardt disease. This study demonstrated the distribution, progression, and intrafamilial variability of Stargardt disease phenotypes associated with this mutation.